Hybrid formulation solution for stress analysis of curved pipes with welded bending joints - Madureira, Luísa (2010)
A method is presented for evaluating the stress intensity factor of part-through cracks in a thin pipe elbow. A hybrid formulation solution is used to evaluate the stress field close to the crack area. The stress field values are then inputted into a previously developed method published in the literature to evaluate the stress intensity factor in cylindrical shells. Results from cylindrical shells with part-through cracks are extended to double-curvature pipe configurations that contain the same kind of flaw.